PENGARUH INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA PROFESI SEBAGAI VARIABEL INTERVENING PADA EMPAT KANTOR AKUNTAN PUBLIK DI KOTA JAKARTA - Crismon Tiodom Sitohang; Harlyn L. Siagian (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2019)
This research was conducted to determine the effect of independence on audit qualitywith professional ethics as an intervening variable. Primary data is a questionnaire distributedto 60 respondents, namely auditors who are in four public accounting firms in the Jakarta area.The sample method used in this study is random sampling and analysis is done by descriptiveanalysis and path analysis used to analyze hypotheses, and also correlation coefficients. Theresults in this study indicate that independence, professional ethics and audit quality have beencarried out well. Independence has a significant effect on audit quality, so does professionalethics have a significant effect on audit quality and independence has a significant effect onprofessional ethics. Furthermore, based on the path coefficient it is shown that independencehas a strong relationship with audit quality when professional ethics have a strong relationshipwith audit quality. Independence has a significant influence on audit quality with professionalethics as an intervening variable. This is because the t-value is greater than the t-table value,which is 12.033> 1.671, with a mediation coefficient of 0.300255. It can be concluded thatprofessional ethics as a moderating variable has significantly affected audit quality.